Biology Learning for Students with Special Needs in Bengkulu City - Belalala, Restite Kalera; Hartati, Merri Sri; Krisnachinda, Sirinun (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to find out how the learning process of children with special needs in the Alam Mahiraschool is depicted and what are the problems in Biology learning for children with special needs and tofind out the Implementation of Biology Learning for Students with Special Needs at Alam Mahira HighSchool, Bengkulu City. Method: This type of research is a qualitative case study method. This studyobserved the implementation of the Biology learning process for students with special needs. Data anddata sources in this study consist of primary data (Biology teachers and students) and secondary data(syllabus and lesson plans). Results: The results of this study indicate that in the general learning processof students with special needs at Alam Mahira High School, Bengkulu City, the learning process forchildren with special needs or autism does not have an accompanying teacher or Shadow teacher, meaningthat these students are already independent because they are already in a high class. However, in theteaching and learning process these students because one of the characteristics of children with specialneeds is difficulty in social forms, so that in the teaching and learning process they are not associated withtheir friends, even though they are in the same class . However, children with special needs have a learningsystem using tutorials and the methods they use are tutorials in nature. This children with special needsstudent, even though he is children with special needs, but his background or interest is indeed cognitive,meaning that he does have a tendency to like learning, because indeed the children with special needs childreally likes cognitive science, because the children with special needs student at Alam Mahira High Schoolis indeed more interested in cognitive science. other sciences such as art and so forth. Conclusion: theresults of the observations of the researcher and the accompanying teacher specifically helping thechildren with special needs, namely the biology teacher, said that the child generally has a very hightendency in the cognitive domain. This can be seen from the results of the report cards of children withspecial needs students whose grades are good.